A synergistic self-assembled 3D PEDOT:PSS/graphene composite sponge for stretchable microsupercapacitors. Issue 2 (2nd October 2019) - Yan, Wenrong; Li, Jinhui; Zhang, Guoping; Wang, Lei; Ho, Derek
Abstract : A novel stretchable MSC with laser-patterned 3D PEDOT:PSS/rGO electrodes synthesized by synergistic self-assembly exhibits excellent specific capacitance and stretchability. Abstract : Microsupercapacitors (MSCs) with excellent flexibility and electrochemical capacitance are promising energy storage devices for wearable electronics. In this paper, we present a 3D porous poly(3, 4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS)/graphene composite sponge (PGCS) fabricated via a facile self-assembly process for highly stretchable, high areal capacitance MSCs. The proposed self-assembly process enables simultaneously the following in one-step: (1) separation of PSS and PEDOT from PEDOT:PSS, (2) reduction of graphene oxide (GO) into reduced graphene oxide (rGO), and (3) integration of PEDOT and rGO into a hybrid 3D composite. By tuning the mass ratio of PEDOT:PSS and GO, PGCSs with different porosities, mechanical properties, conductivities, and capacitances can be obtained. With the incorporation of PEDOT into rGO, the PGCS exhibits enhanced electrochemical performance and better mechanical flexibility. The fabricated stretchable MSC exhibits a high areal specific capacitance (19.3 mF cm −2 at a scan rate of 20 mV s −1 ), good electrochemical stability (88.6% retention of specific capacitance after 5000 cycles), and a remarkable stretchability (87.1% retention of specific capacitance after 50% stretching). This facile approach provides a general strategy for synergistic self-assembly of composite sponges and the design of stretchable 3D MSCs, suitable for energy storage devices with high stretchability and high energy density.